Development and Application of University Information Service - Chun Yu; YanXia Li; Fang Yuan; Qian Zhang; Xi Chen (Institute of Advanced Engineering and Science, 2014)
The current situation and existing problems in university informationisation was given briefly, with object of university information service development. It proposed the method to develop information service, including both model design and technology realization on basis of main database. A system, which covers the core data resource of the university and implements one-stop information service has been designed and realized. Integrated with R-ABAC, Portal and dynamic reports, it provided comprehensive inquiry and statistical analysis service of all kinds of information for all the teachers, students and all levels of managerial staff, which applied in individual management, business management and decision making, which serves talents training, the basic task of universities. DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.4948